Kecernaan Pelepah Sawit Fermentasi dalam Complete Feed Block (CFB) untuk Sapi Potong - Armina Fariani; Arfan Abrar; Gatot Muslim (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Palm midrib that was one of all agroindustries unused. It could be pontential as animal feeding. It could used as animal feeding with made it Complete Feed Block (CFB). This research aimed to study the fermentation of  palm  midrib in complete feed block (CFB) on the quality of degestibility in vitro. The research was conducted three phases, the first phase of the fermentation of  palm  midrib grounding  with White Root Fungy, the second stage of the manufacture of complete feed block (CFB) and the third stage of the proximate analysis and digestibility analysis, The research was in  Nutrition  and animal feeding  Laboratory,  Agriculture Faculty, Srivijaya University. This research used Completely Randomized Design (CRD) with two treatments and five replications consisting of Formula 1 and Formula 2, the parameters were observed dry matter, crude fiber, crude protein, Extract Either, BETN, dry matter digestibility coefficients, organic matter digestibility coefficients and the concentration of N-NH 3. The result of CFB formulation  were formula 1 TDN: crude protein (47.32%: 13.93%), formula 2 (48.41%: 7.96%), where the results of proximate analysis showed F1: 98.66% DM, LK 13:19%, 7:03% PK, SK 35.79%, 40.24% BETN, and F2: 98.41% DM, LK 16:43%, PK 6.25%  SK 24.06%, 49.50% BETN. Formulations showed that all treatments influence  non significantly (p> 0.05),  organic matter digestibility (85.00% vs. 85.70%), dry matter digestibility (59.42% vs. 59.62% vs. 16.72%) and the concentration of N-NH 3 (2.2% versus 1.8 %). The conclusion of this study is the complete feed block (CFB) can be used as a ruminant animal feeding, but should pay attention to aspects of quality and palatability.